Medication Errors During Treatment with New Oral Anticancer Agents: Consequences for Clinical Practice Based on the AMBORA Study. Issue 4 (18th July 2021) - Schlichtig, Katja; Dürr, Pauline; Dörje, Frank; Fromm, Martin F.
Abstract : Patients treated with oral anticancer agents (e.g., kinase inhibitors) are a high‐risk population for medication errors due to, for example, polymedication, age, and limited adherence. Systematic evaluations regarding frequencies and causes of medication errors and resulting harm are lacking. Our previously published multicenter randomized AMBORA trial revealed that an intensified support by clinical pharmacologists/pharmacists for patients and the treatment team considerably reduced drug‐related problems and improved patient‐reported outcomes. Using this database, we performed a comprehensive, additional analysis focusing on medication errors related to the patients' complete medication with consideration of the antitumor agents, concomitantly administered drugs, and herb/food intake. Two hundred two patients starting a new oral anticancer drug regardless of the tumor entity were included. Clinical pharmacologists/pharmacists performed advanced medication reviews for 12 weeks. Medication errors were characterized regarding type, cause, patient harm, and the involved medicines. We detected 1.7 medication errors per patient (335/202). Of the medication errors (216/335), 64.5% occurred within the concomitant medication. Patients caused 28.4% of the medication errors. There were 67.8% detected immediately after the start of the new oral regimen, and 14.9% resulted in temporary harm. Drug‐drug or drug‐food interactions accounted for 24.8% of the medication errors. Patients and physicians need to be addressed in strategies for systematic reduction of medication errors during treatment with new oral antitumor drugs. Clinical decision support systems focusing on drug‐drug interactions capture only a minority of the medication errors. Specialists with expertise in clinical pharmacology/pharmacy should support both the treating physicians as well as the patients for improved patient safety.